Inbound tourism in Malaysia: unlocking the potential traveling experience of European and Oceanian tourists - Saad, Mazni; Abdul Latif, Samshul Amry; Sahar, Rafidah; Hasan, Mohmed Razip; Ahmed Mian, Ejaz (AMER-ABRA cE-Bs by e-International Publishing House, Ltd. UK., 2022)
This study explores the memorable traveling experience (MTE) of 143 tourists from Europe and Oceanian in Malaysia. The researchers conducted a survey to investigate the factors that influence their revisit intention to Malaysia as an attractive destination. Partial least square structural equation modeling (SEM-PLS) results indicated that tourist attitudes, destination images, electronic Word of Mouth (eWOM), and perceived quality have positive and significant influences on travel intention. However, the eWOM failed to mediate the tourists’ attitudes, perceived quality, and destination image towards their revisit intentions.